ANALISIS PERBANDINGAN USAHATANI KARET PROGRAM REGU RPBSK DAN USAHATANI KARET RAKYAT DI KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Mahyudi, Fitri (Chlorophyl, 2022)
This research aim to to comparison analyse of Rubber Effort Program RPBSK and People Rubber Effort Tanah Bumbu Regency South Kalimantan Province with revenue rubber effort variable, Rubber Area Tap, Crop Economic Age, Production and Rubber Revenue. The results of the research showed that rubber area tap much better with RPBSK Program, Longer crop economic age, higher rubber production and higher rubber revenue with RPBSK compared to non-RPBSK program. Earnings obtained by farmer responder in one month equal to Rp. 11.427.510, compared to non RPBSK farmer earnings mean of Rp. 6.117.097,26